Quality of care and suspected developmental delay among children aged 1-59 months: a cross-sectional study in 8 counties of rural China - Chenlu Yang; Xiaoli Liu; Yuning Yang; Xiaona Huang; Qiying Song; Yan Wang; Hong Zhou (BMC, 2019)
Abstract Background The data about quality of care of more than 70 countries were available from UNICEF but little was known about China. We examined the status about quality of care and explored its associations with developmental outcomes in Chinese children. Methods A cross-sectional study with probability proportional to size sampling method was conducted in 8 counties of rural China. A total 1927 children were assessed on development status using Ages and Stages Questionnaires-Chinese (ASQ-C) based on Chinese normative data. Nutritional status was derived from the anthropometric method following WHO guidelines. Caregivers were interviewed through household questionnaires from UNICEF's 5th Multiple Indicator Cluster Survey to understand the quality of care, including the status of availability of children's books, availability of playthings, support for learning, fathers' support for learning and inadequate care. Moreover, quality of care was explored to be categorized into three levels (poor, medium and good) for overall assessment. Multivariable logistic regression model was applied to estimate the odds ratios and 95% confidence intervals between quality of care and suspected developmental delay (SDD) after adjustment for potential confounding variables. Results The proportions of availability of children's books, playthings, support for learning, fathers' support for learning and inadequate care were 36.8, 91.3, 83.1, 16.4 and 4.9%, respectively. When compared to available data of more than 70 countries and areas, the quality of care in rural China was in the middle to upper level. After adjustment for potential confounding variables, multivariable analysis showed that SDD in overall ASQ remained negatively associated with availability of children's books (odds ratio [OR] and 95% confidence interval [CI]: 1.64 [1.27-2.12]), playthings (OR and 95% CI: 2.23 [1.52-3.27]) and support for learning (OR and 95% CI: 1.81 [1.06-3.10]). When compared with children under good quality of care, children under medium and poor quality of care had higher prevalence of SDD in overall ASQ (OR and 95% CI: 1.59 [1.21-2.07]; 3.05 [1.96-4.74]). Conclusions Quality of care in rural China still had scope for improvement. Better quality of care had negative associations with SDD.